Analisis Penerapan Kaidah Taqdim-Ta’khir dalam Tafsir Al-Munir Karya Wahbah al-Zuhaili - Rohimatil Umah, Fina Nuriah; Hartono, Hartono (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
Al-Qur'an as Godly words is believed to have beyond-humanistic literary values. In the Qur'an, there are words whose unusual arrangement with sentences that should have ended actually came first and vice versa. The wording in the Qur'an is arranged in such a way for a reason. An exegesis work by Wahbah al-Zuhaili, Tafsir Al-Munir, has tried to explain such aspects of the Qur'an, including the rules of taqdim and ta'khir, which significantly influences the Qur'an verses understanding. Focusing to explore the application of the rules as advised in Tafsir al-Munir, this literature study research will present several examples of interpretation in Tafsir al-Munir. Wahbah al-Zuhaili explains that among the purposes of taqdim and ta'khir in the Qur'an is to glorify, to prioritize, to specialize, and to show the superiority of something. Therefore, the rules have clearly great influence on the understanding of the Qur'anic verses.